Redescription of two species and a new distribution record for China of the genus MelanogryllusChopard, 1961 and a report of one new species of the genus Velarifictorus Randell, 1964 (Orthoptera: Gryllidae; Gryllinae) - Wang, Ning; Huang, Huateng; Ma, Li-Bin (Zootaxa, 2023)
Dark body color is very common among crickets, and this article discusses four species of black field crickets with distinct distributions. There are three species of the genus Melanogryllus Chopard, 1961 and one species of the genus Velarifictorus Randell, 1964. Of them, Melanogryllus chopardi Bey-Bienko, 1968 was discovered in Southwest Xizang, on the border between China and Nepal; Melanogryllus desertus (Pallas, 1771) was primarily found in arid regions of northwestern China; Melanogryllus bilineatus Yang & Yang, 1994 was often collected from the Southeast China coastal region; and the last species, Velarifictorus yuanilandrevus sp. nov., is a new species that was collected in Yunnan, a province in Southwest China. In addition, the new species could be distinguished from the others by its black body coloration and the absence of yellow stripes on the head. Here, we describe these species in detail, with photographs of the genitalia, and provide a distribution map for them and keys for Chinese Melanogryllus species.